Validation of SARAL/AltiKa significant wave height and wind speed observations over the North Indian Ocean. (December 2015) - Kumar, U. Mahesh; Swain, D.; Sasamal, S.K.; Reddy, N. Narendra; Ramanjappa, T.
Abstract: SARAL/AltiKa, a joint Ka-band altimetry mission of the Centre National d'Etudes Spatiales (CNES) and Indian Space Research Organisation (ISRO) was successfully launched on February 25, 2013. The main purpose of this mission is to explore the ocean surface topography. As it is a Ka-band altimeter mission unlike other altimeters which were primarily in Ku-band, it is essential to calibrate and validate AltiKa data products before using the data for oceanographic applications. With this objective, two important geophysical parameters, Significant Wave Height (SWH) and Wind Speed (WS) from SARAL/AltiKa are inter-compared with those from 18 moored buoy stations in the North Indian Ocean (NIO) for a two year period from March 2013 to March 2015. SARAL/AltiKa GDR-T patch-2 version products are collocated with moored buoy observations with a collocation criteria of spatio-temporal window of 50 km radius about the buoy location and 30 min time for all the altimeter measurements. Following this, linear regression relations are developed and statistical analyses carried out to assess the performance of SARAL/AltiKa. The correlation between SARAL/AltiKa derived SWHs and those from moored buoys is 0.98 m with a bias of −0.02 m and Root Mean Square Error (RMSE) of 0.15 m at 95% confidence level. The WSs derived from SARAL/AltiKa Ka-band correlates reasonably well with buoy observations with a correlation coefficient of 0.91, bias of −0.28 m/s and RMSE of 1.13 m/s. The inter-comparison results are found to be interesting with a good agreement between SARAL/AltiKa and moored buoys observations of SWH and WS in the NIO where SWHs are less than ∼4 m and WS are less than ∼13 m/s during the entire analysis period. Highlights: The SWH values from moored buoys and the AltiKa are consistent with each other. AltiKa derived WSs are reasonably good relative to buoy winds. First time launched Ka-band altimeter shows good potential for SWH, WS estimations.